Rational approaches for the design of effective human immunodeficiency virus type 1 nonnucleoside reverse transcriptase inhibitors - Ribone, Sergio Roman (2011)
The binding of several classes of nonnucleoside reverse transcriptase inhibitors (NNRTIs) to wild-type (wtRT) and K103N mutant (mRT) human immunodeficiency virus type 1 (HIV-1) reverse transcriptase is studied by molecular dynamics and energy decomposition techniques. The imidoylthiourea (ITU), diaryltriazine (DATA), and diarylpyrimidine (DAPY) NNRTIs studied maintain the hydrogen bond with Lys101 during the 3 ns molecular dynamics trajectories. When bound to mRT, all the DAPYs studied establish hydrogen bonds with Glu138; among these, those of the potent inhibitors TMC120 and TMC125 are water-mediated. The molecular interactions of the NNRTIs in the binding pocket are correlated to the drugs' potency. Quantitative free energy analyses show a linear relationship between the van der Waals energetic component and the potency against wtRT. The molecular basis of the interaction between NNRTIs and RT presented here provide quantitative approaches for the design of novel effective anti-HIV drugs.